Effect of defoliation frequency on Rytidosperma virescens plants and arbuscular mycorrhizal fungi colonization - Toledo, Santiago; Fontenla, Sonia Beatriz; Peri, Pablo Luis (Elsevier, 2022)
Rangelands provide different ecosystem services to satisfy human needs. Although grazing management in southern Patagonia is mostly characterized by extensive continuous grazing, rotational grazing management may improve plant productivity and its associated microbiome. Arbuscular mycorrhizal (AM) symbioses play an important role in the functioning of arid rangelands. However, in most arid and semiarid grasslands, little is known about the environment-plant-symbiont interaction under different defoliation frequencies and contrasting growth conditions. In this context, the objective of the present study was to evaluate the response of Rytidosperma virescens native grass and the associated AM fungi under different defoliation frequency treatments (plants undefoliated, two clippings with 50-d intervals between defoliations, four clippings with 30-d intervals, and six clippings with 21-d intervals) and two growth conditions (field and greenhouse) in a 150-d experiment. Defoliation frequency with 21-d clipping intervals negatively affected plants and AM colonization. We found a negative linear relationship between AM colonization and removal of aboveground biomass and a positive relationship with root biomass and leaf area of R. virescens plants. We determined that the appropriate recovery period for rotational grazing systems should be at least 50 d (threshold) to optimize forage production and AM symbiosis during spring-summer seasons. Sustainable grazing management practices should be designed to improve or restore AM communities to maintain positive feedback with plant development.